A Bibliometric Analysis of the Possible Convergence of Heterodox Associations. Issue 1 (2nd January 2023) - Almeida, Felipe; Cruz-e-Silva, Victor; Brites, Maríndia
Abstract: This article is a study on the possible common theoretical approaches shared by three heterodox associations-Association for Evolutionary Economics (AFEE), Union for Radical Political Economics (URPE), and Association for Social Economics (ASE). We analyze their closeness and potentially common approaches as reported in papers published by the associations' main journals from 2010 to 2019. Using bibliometrics, the papers are analyzed in terms of convergent issues shared by these heterodox associations. Our article concludes, first, that building alternative approaches based on a criticism of both mainstream and New Institutional Economics is a possible point of convergence for AFEE, URPE, and ASE. Second, criticism of capitalism and studies on economic development could act as a convergence point for AFEE and URPE. Third, ASE seems to be more open to heterodox approaches than AFEE and URPE, and can make room for other convergence points. However, the ASE-AFEE and ASE-URPE dyads have not yet explored such opportunities for convergence.